2019
DOI: 10.14744/nci.2019.95676
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serum iris level and inflammatory markers in Fibromyalgia Syndrome

Abstract: OBJECTIVE:In the present study, we aimed to compare serum irisin levels in patients with fibromyalgia syndrome (FMS) and healthy control subjects and also investigate the relationship between irisin, disease activity and inflammation markers in patients.METHODS:A total of 84 women, including 48 patients who were diagnosed with FMS and 36 healthy controls, were included in this study. The demographic characteristics of the patients and control group were recorded. VAS for pain and the Fibromyalgia Impact Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…IL-1β's association with fibromyalgia pathophysiology has been the subject of both human and animal studies. The results of several studies have shown the presence of increased levels of IL-1β in patients diagnosed with fibromyalgia compared to controls, giving some support to this linkage [ 17 , 22 ]. One study demonstrated that using a low dose of naltrexone (an atypical anti-inflammatory drug) for eight weeks diminished the overall symptomatology of fibromyalgia by 18% and also showed a 15% reduction of related pain.…”
Section: Reviewmentioning
confidence: 99%
“…IL-1β's association with fibromyalgia pathophysiology has been the subject of both human and animal studies. The results of several studies have shown the presence of increased levels of IL-1β in patients diagnosed with fibromyalgia compared to controls, giving some support to this linkage [ 17 , 22 ]. One study demonstrated that using a low dose of naltrexone (an atypical anti-inflammatory drug) for eight weeks diminished the overall symptomatology of fibromyalgia by 18% and also showed a 15% reduction of related pain.…”
Section: Reviewmentioning
confidence: 99%
“…Skeletal muscle secretes the hormone irisin in response to physical exercise; this hormone has been linked to several positive effects on energy metabolism. Irisin acts as a messenger in white adipose tissue, modifying its phenotype to beige adipocyte, enhancing adipocyte thermogenic capacity [57,58]. Evidence points to an association between irisin secretion rising with an improvement in glucose and insulin metabolism.…”
Section: Discussionmentioning
confidence: 99%